Reducing Zinc and Chromium in Wastewater Treatment Biosolid Through Sulfuric Acid Extraction - Mu’tassim Billah; Disty Nur Rohmah; Faisal Amri Sholahuddin; Renova Panjaitan; Kindriari Nurma Wahyusi; Retno Dewati (Future Science, 2022)
The separation of heavy metals, zinc (Zn) and chromium (Cr), in biosolid waste can be carried out by an extraction process using H2SO4 as a solvent. The extraction process was carried out with a variation of time agitation and sulfuric acid concentration. The extracted cake was then analyzed using the atomic absorption spectrophotometry (AAS) method. The most effective reduction in Zn and Cr levels was obtained at 120 minutes and a solvent concentration of 1.5M with an efficiency of 98.80% and 97.89%, respectively.